'Think of the future': Managing educational change from students' perspectives of an undergraduate sustainable business programme. Issue 2 (July 2017) - Warwick, Paul; Wyness, Lynne; Conway, Hugh
Abstract: This paper explores how partnership with students can help sustainability educators with refining the living theory of their practice and improving the implementation of this practice in real world contexts. It draws from the case study of an undergraduate module within a UK Higher Education Institution committed to the Principles for Responsible Management Education (PRME) and that has sought to embody a shift towards more active, student-centred and problem-based pedagogical approaches. The module leaders aimed to draw out a more nuanced appreciation of the knowledge, skills, values, and attributes necessary for business and management graduates to contribute to more sustainable futures. We argue that whilst attempts to reform higher education in this direction are on the rise worldwide, there remains a relative lack of research into the students' perspectives of these Education for Sustainable Development initiatives. Drawing from the applied research work of Swanson and Chermack (2013) and Kim-Eng Lee and Mun Ling (2013), it is argued that robust strategies for listening to students provide a vital praxis lens through which the intended, enacted and lived curriculum can be refined and brought closer together by business school educators. Highlights: Students have a vital role to play as integrated catalysts for educational change with regard to PRME. Implementation research strategies help identify context specific improvements for PRME initiatives. Business Schools can enhance sustainability learning through student centred, problem based and multidisciplinary pedagogies.